Immunomodulatory Properties of Natural Extracts and Compounds Derived from Bidens pilosa L.: Literature Review - Xandy Melissa Rodríguez-Mesa; Leonardo Andres Contreras Bolaños; Antonio Mejía; Luis Miguel Pombo; Geison Modesti Costa; Sandra Paola Santander González (Pharmaceutics, 2023)
Bidens pilosa L. has been used in different parts of the world mainly to treat diseases associated with immune response disorders, such as autoimmunity, cancer, allergies, and infectious diseases. The medicinal properties of this plant are attributed to its chemical components. Nevertheless, there is little conclusive evidence that describes the immunomodulatory activity of this plant. In this review, a systematic search was carried out in the PubMed-NLM, EBSCO Host and BVS databases focused on the pre-clinical scientific evidence of the immunomodulatory properties of B. pilosa. A total of 314 articles were found and only 23 were selected. The results show that the compounds or extracts of Bidens modulate the immune cells. This activity was associated with the presence of phenolic compounds and flavonoids that control proliferation, oxidative stress, phagocytosis, and the production of cytokines of different cells. Most of the scientific information analyzed in this paper supports the potential use of B. pilosa mainly as an anti-inflammatory, antioxidant, antitumoral, antidiabetic, and antimicrobial immune response modulator. It is necessary that this biological activity be corroborated through the design of specialized clinical trials that demonstrate the effectiveness in the treatment of autoimmune diseases, chronic inflammation, and infectious diseases. Until now there has only been one clinical trial in phase I and II associated with the anti-inflammatory activity of Bidens in mucositis.